Agreement between Components of Composite Predicate in Modern Armenian - SARKISYAN, ARTASHES (Bulletin of Yerevan University B: Philology, 2021)
In modern Armenian, there can be an agreement between the components of the composite predicate. It is mostly expressed bycategories of person, number, and negation. The agreement is used when one of the components of the composite predicate is expressed by a personal pronoun, negative pronoun or by a word which has a category of person, by adding an article.
Keywords: agreement, compound predicate, category of person, category of number, personal pronoun, negative pronoun